Correction: Anup C. Katheria. Neonatal Resuscitation with an Intact Cord: Current and Ongoing Trials. Children 2019, 6, 60 - Anup C. Katheria (MDPI AG, 2019)
The author wishes to make the following corrections to this paper [...]